COMPARISON OF INTRACORONARY EPINEPHRINE TO STANDARD TREATMENTS ALONE FOR REFRACTORY CORONARY NO-REFLOW IN STEMI PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION - SAOOD , Y; SALMAN, A; KHAN , MI; ASIM, M (Biological and Clinical Sciences Research Journal, 2023)
Refractory no-reflow is a serious primary percutaneous coronary intervention (PPCI) complication in ST-segment elevation myocardial infarction (STEMI) patients associated with worse clinical outcomes. Intracoronary epinephrine has been suggested as a potential adjunctive therapy to improve myocardial perfusion in these patients, but its efficacy and safety remain unclear. This study included 58 STEMI patients with refractory no-reflow during PPCI treated with either intracoronary epinephrine or conventional treatments alone. The primary outcome was the improvement in myocardial perfusion assessed by the TIMI frame count at the end of the procedure. Secondary outcomes included rates of adverse cardiovascular events and clinical outcomes at 30 days. Intracoronary epinephrine was associated with significantly improving myocardial perfusion compared to conventional treatments alone (mean TIMI frame count 24.1 ± 6.7 vs. 33.6 ± 7.9, p < 0.001). This benefit was consistent across all subgroups of patients with TIMI 0-1 flow. Patients treated with intracoronary epinephrine had significantly lower rates of adverse cardiovascular events at 30 days than those who received conventional treatments alone (12.5% vs. 43.8%, p = 0.02). The two groups had no significant differences in major bleeding, recurrent myocardial infarction, or all-cause mortality. Based on the results, the use of intracoronary epinephrine during PPCI in STEMI patients with refractory no-reflow is associated with improved myocardial perfusion and lower rates of adverse cardiovascular events. These findings support the use of intracoronary epinephrine as a safe and effective adjunctive therapy in this population, but further studies are needed to determine optimal dosing and timing of administration.